The cabin : inspiration for the classic American getaway - Mulfinger, Dale, 1943- (Taunton Press, 2001)
This book presents the best that cabin living has to offer through stunning photographs, site plans, floor plans, and profiles of over 35 inspirational cabins from all over America.